Is stakeholder orientation relevant for European firms?. Issue 6 (December 2016) - Patel, Vijay K.; Manley, Scott C.; Hair, Joseph F.; Ferrell, O.C.; Pieper, Torsten M.
Abstract: Stakeholder theory suggests firms should be sensitive to a broad group of stakeholders and their needs, with balanced trade-offs that are fundamental to achieving sustainable competitive advantage, and ultimately survival. Market orientation (MO) scholars also consistently call for inclusion of a broader group of stakeholders than the widely studied customer and competitor groups to better understand the impact of multiple stakeholders on firm performance. In response, this study expands the traditional domain of MO and defines overall stakeholder orientation as including customers, competitors, employees and shareholders, designating them as 'core and essential stakeholders.' Scholars have also advocated the inclusion of more forward-looking, proactive considerations in the conceptual framework to complement the usual responsive aspects of MO. Measures for both proactive and responsive orientations for the four core stakeholder groups, representing overall stakeholder orientation, were developed and validated. Findings show that for European firms proactive considerations are potentially more impactful than responsive, and overall stakeholder orientation is a significant predictor of improved financial and non-financial performance.